2020
DOI: 10.1038/s41598-020-58896-6
|View full text |Cite
|
Sign up to set email alerts
|

Spirulina maxima extract prevents activation of the NLRP3 inflammasome by inhibiting ERK signaling

Abstract: Spirulina maxima extract prevents activation of the NLRP3 inflammasome by inhibiting ERK signaling Sungwoo chei, Hyun-Ji oh, Ji-Hyeon Song, Young-Jin Seo, Kippeum Lee, Kui-Jin Kim & Boo-Yong Lee * The blue-green alga Spirulina maxima is a microscopic filamentous cyanobacterium. Spirulina was recently reported to elicit beneficial effects such as reducing cholesterol and inducing weight loss; however, its effects on inflammation are unknown. To determine the effect of S. maxima extract (SMe) on innate immunity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…We also determined the effects of age and KRGSF treatment on the expression of genes encoding components of the NLRP3 inflammasome, which can be activated by ROS [12,29]. The genes encoding NLRP3, ASC, IL-1β, and caspase-1 were all expressed at higher levels in 12-month-old than in 6-month-old untreated mice, but these effects were ameliorated by KRGSF treatment.…”
Section: Discussionmentioning
confidence: 99%
“…We also determined the effects of age and KRGSF treatment on the expression of genes encoding components of the NLRP3 inflammasome, which can be activated by ROS [12,29]. The genes encoding NLRP3, ASC, IL-1β, and caspase-1 were all expressed at higher levels in 12-month-old than in 6-month-old untreated mice, but these effects were ameliorated by KRGSF treatment.…”
Section: Discussionmentioning
confidence: 99%
“…C2C12 cell pretreated with GEF (0, 20, 100 µg/mL) for 4 h, and stimulated with heat for 12 h. The culture supernatants were collected and mixed 100 µL Griess reagent (Merck Millipore, Burlington, MA, USA). After 15 min, the level of nitric in culture supernatant was measured by ELISA in 570 nm [32].…”
Section: Nitric Oxidative (No) Assaymentioning
confidence: 99%
“…The use of cyanobacterium Spirulina based nutraceuticals is well explored in in-vitro and clinical studies and is commercially available. Spirulina -based nutraceuticals have been reported to boost innate and adaptive immunity [18] , [19] , [20] , and possess antiviral properties against different enveloped viral infections such as human immunodeficiency virus (HIV) and herpes simplex virus (HSV) [21] , [22] , [23] , [24] . This review discusses the potential therapeutic role of algae-based, Spirulina nutraceuticals in addressing the SARS-CoV and related viral infections.…”
Section: Introductionmentioning
confidence: 99%
“…The NLRP3 inflammasome activation plays an important role in the innate immune response to pathogenic infections in macrophages including COVID-19 [ 34 , 35 ]. Spirulina extracts (SE) are found to prevent the activation of NLRP3 inflammasome through the inhibition of extracellular signal-regulated kinases (ERK) signaling [18] . Chei et al recently reported the anti-inflammatory effect of Spirulina maxima extracts (SE) on mouse RAW264.7 macrophages and human THP-1 cells [18] .…”
Section: Introductionmentioning
confidence: 99%